La terapia ocupacional y su relación con la autoestima de los estudiantes con discapacidad intelectual que asisten a la fundación de enseñanza individualizada para niños, niñas y adolecentes “E.I.N.A.” de la ciudad de Quito. En el período 2013-2014. Lineamientos propositivos - DÁVILA BASTIDAS, MARICEL DEYANIRA (2015)
This research entitled: OCCUPATIONAL THERAPY AND ITS RELATION TO SELF-ESTEEM OF STUDENTS WITH INTELLECTUAL DISABILITIES ATTENDING THE INDIVIDUALIZED EDUCATION FOUNDATION FOR CHILDREN AND TEENS "E.I.N.A." QUITO CITY IN THE PERIOD 2013-2014. GUIDELINES PROACTIVE. In the present investigation the overall objective was to determine the relationship between occupational therapy and self-esteem of students with Intellectual Disability Foundation of individualized instruction for children and teenagers “EINA” The methods used in this research were: Scientist, Analytical - Synthetic, Inductive and Deductive, Descriptive and Statistical Model . The techniques and tools that were applied were: a survey of occupational therapists of " EINA " foundation in order to identify the type of occupational therapy students receive with Intellectual Disabilities , obtaining results that respondents Occupational Therapists in 100 % the type of occupational therapy that takes place in the foundation are : activities of daily living , activities in the area of education , recreation and leisure activities , 67 % say that engages in such work and social participation , and 33 % engage in sports activities . The second instrument was a Self-Esteem Test Cirilo Toro Vargas, applied to students with Intellectual Disability "E.I.N.A." foundation in order to assess the level of self-esteem, and the results concluded that 57 % have a positive self-esteem and high 43% have a positive Low Self-Esteem .